Algunas reflexiones sobre los límites del oikoumene en el Imperio Romano - María José Hidalgo de la Vega (Gerión, 2005)
This paper reflects on the Roman Empire as pattern of a world-wided politycal system former to the contemporary globalization. The analysis of this hegemonic order can help to understand rather our present.